Understanding the Objectives, Fit, and Leveraging of Touch New Zealand’s Sponsors - Thompson, Nathan (Auckland University of Technology, 2023)
While there is a growing body of research on sport sponsorship, relatively little attention has been given to National Sport Organisations (NSOs) as a unique organisational type with sponsor relationships. Thus, this study represents a novel and important contribution to the literature. The aim was to explore (a) objectives of NSO sponsors; (b) NSO sponsor perceptions of fit; and (c) sponsor leveraging activity. A qualitative approach was implemented, and the findings are based on semi-structured interviews with eight sponsors associated with Touch New Zealand. The study was divided into two phases. In Phase 1, interviews were conducted with sponsors of Touch New Zealand. A deductive thematic analysis was used to generate insights from the interviews in these specific areas. Phase 2, a content analysis, was carried out to explore sponsor leveraging activities. The findings revealed that branding was the most prominent and important objective for sponsors highlighting the importance of leveraging their sponsorship investment to enhance brand awareness and identity. Community involvement seemed to be the most important objective for some sponsors. Meanwhile, business to business relationships and new customer acquisition opportunities to generate leads were for others, as well as media exposure. NSO’s seeking to nurture effective sponsorship arrangements must be actively thinking about and improving their own brand, such that it will align with potential sponsors. NSOs should also consider how they can create opportunities for sponsors to realise their business objectives around market share and return on investment (ROI). Future studies should replicate this project in diverse settings and contexts including across different sports, countries, and levels of competition. Further, studies should seek to look more comprehensively at the leveraging efforts across the sponsors of multiple NSOs.